Bodies that migrate. Social and cultural displacements in Victor Hugo Viscarra and Susy Shock - Miranda, Ana Lía (2021)
The issue of migration is a fundamental factor in Latin American literature, because it allows us to investigate the actions of subjects who experience the phenomenon in many ways. I am interested in examining the literary expressions of Victor Hugo Viscarra, written from the periphery of Peace (Bolivia) and Susy Shock (Argentina) which is defined as a “trans-Sudaca artist”, because they show physical mobility and in their modes of knowledge and condition.The writing spaces that are defined can be read from the categories of “migrant subject” and “heterogeneity” worked by Antonio Cornejo Polar and Raúl Bueno. In turn, Susy Shock's transvestite body functions as a destabilizer of the heteronormative order, diving in the interstices of the binary opposition of the genus showing itself as a body that redefines in each performative representation, that is, in its voice and writing, other processes of displacement.